Relationship Between Learning Style and Students’ Cognitive Ability In Chemistry Subjects - Kurniawati, Yenni; Diva; Lina, Ejma Rukma; Nabillah, Marwana; Sari, Ceria Purnama (Universitas Papua, Manokwari, Indonesia, 2024)
The diverse characteristics of chemistry materials require attention to the needs of one of them, namely the tendency of learning styles that students have, for that learning style is something that needs to be studied in relation to students' cognitive abilities. The purpose of this study was to determine the relationship between learning styles and chemistry cognitive abilities of Madrasah Aliyah Negeri Kampar students. Learning style data obtained from questionnaire scores, interviews and observations of students, the value of cognitive abilities obtained from the test results of students' chemistry cognitive abilities on atomic structure material. subject of this research is Madrasah Aliyah Negeri Kampar students, while the object of research is the relationship between learning styles with students' cognitive abilities in chemistry subjects. The sample in this study was taken from class X IPA 1 which amounted to 30 people.. Sampling in this study using purposive sampling technique. Data collection was done through observation, questionnaires, interviews, tests, documentation. The results of this study indicate that students with visual learning style tendencies are more than audio learning style tendencies followed by kinesthetic learning style tendencies and students with visual learning style tendencies on atomic structure material have better cognitive ability scores. Furthermore, the data from the observation of the relationship between learning styles and students' chemistry cognitive abilities were tested using product moment correlation. The results of data processing obtained rxy = 0.838 > rt = 0.361, this means Ha is accepted and Ho is rejected. So that there is a positive and significant correlation between the learning style variable and the variable cognitive abilities of students in chemistry subjects Madrasah Aliyah Negeri Kampar